An updated checklist and literature review of Harpellales (Kickxellomycotina) and other endobionts associated with the guts of arthropods from Argentina - López Lastra, Claudia Cristina (2022)
The objective of this work is to further the knowledge of gut fungi, inhabiting the digestive tract of mandibulated arthropods, traditionally the Trichomycetes (currently Kicksellomycotina), in Argentina. The geographical distribution of these endobionts, especially in aquatic insects, but also other arthropods, is updated as well as host records and site information. Fungal species (Harpellales), which mostly colonize immature stages of aquatic insects, were identified in members of Coleoptera, Diptera, Ephemeroptera, Plecoptera, and Trichoptera from different biogeographical regions, from the far North in Jujuy province to the southernmost point in Tierra del Fuego. The overall goal of this review is to consolidate all the published and unpublished records from the country in order to summarize their geographical distribution.